2016
DOI: 10.1021/acs.macromol.6b01496
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Plastics and Elastomers from Renewable Rosin via “Living” Ring-Opening Metathesis Polymerization

Abstract: Utilization of biomass for commodity polymers has gained tremendous interest. We report a method to prepare high molecular weight renewable homopolymers and block copolymers derived from natural rosin. Monomers with high renewable content (70 wt %) were prepared via a simple esterification reaction between dehydroabietic alcohol and 5exo-norbornenecarboxylic acid. Living and controlled polymerization of these monomers were achieved by ring-opening metathesis polymerization to obtain polymers with molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 62 publications
3
77
0
Order By: Relevance
“…Ganewatta et al . prepared thermoplastic elastomers from natural rosin and modified vegetable oil, and discussed other sustainable elastomers from renewable biomass . Plant based phenolic acids with varying functionalities were utilized to prepare thiol‐ene elastomers using a photoinitiator …”
Section: Sustainable Rubbers and Rubber Like Materialsmentioning
confidence: 99%
“…Ganewatta et al . prepared thermoplastic elastomers from natural rosin and modified vegetable oil, and discussed other sustainable elastomers from renewable biomass . Plant based phenolic acids with varying functionalities were utilized to prepare thiol‐ene elastomers using a photoinitiator …”
Section: Sustainable Rubbers and Rubber Like Materialsmentioning
confidence: 99%
“…They showed that TPEs with high elastic recovery could be developed by using these novel monomers. 18 Similarly, supramolecular TPEs owe their bulk properties to the, so called, microphase separation between the hard and the soft domains in the structure, where hard domains are usually formed by inclusion of H-bonding modules (as an example of supramolecular interactions) within the polymer backbones. Therefore, polymer properties can be tailored with aptly selection of hydrogen bonding motifs such as ureidopyrimidinone (UPy, a quadruple H-bonding motif), which is easily introduced into polymer chains either as end-groups or as pending groups (K dim = 6 × 10 7 M −1 in chloroform) with strong tendency to form H-bonds through a quadruple array of H-bonding donors and acceptors (DDAA).…”
Section: Among Common Tpes Linear Triblock Copolymers Has Recentlymentioning
confidence: 99%
“…Next these high‐Tg polymers were used to design TPEs with a soft middle block derived from soybean oil. They showed that TPEs with high elastic recovery could be developed by using these novel monomers . Similarly, supramolecular TPEs owe their bulk properties to the, so called, microphase separation between the hard and the soft domains in the structure, where hard domains are usually formed by inclusion of H‐bonding modules (as an example of supramolecular interactions) within the polymer backbones.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Because in contrast to ketones, 13 aldehydes 14 and esters, 15 which easily engage in reactions with reductive agents, carboxylic acids are generally unreactive. 16 On the other hand, although lithium aluminium hydride was widely used as a strong reductant in carboxyl reduction, 17 its poor chemical selectivity, ammability and explosive nature are unfavorable for large-scale production. Kamochi and Kudo reported the reduction of aryl carboxylic acid derivatives and some aliphatic carboxylic acids using SmI 2 , 18,19 however this strategy was low yielding and limited in scope for aliphatic carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%